Adjusting the Coordination Environment of Mn Enhances Supercapacitor Performance of MnO2. Issue 32 (3rd July 2021) - Zhang, Anqi; Zhao, Rui; Hu, Lingyuan; Yang, Ru; Yao, Shuyun; Wang, Shiyu; Yang, Zhiyu; Yan, Yi‐Ming
Abstract: The electrochemical properties of transition metal oxides strongly depend on the coordination environment of metal atoms. Nevertheless, the relationship between the coordination environment of metal atoms and electrochemical performance of metal oxides is unclear, while the strategy of adjusting the coordination environment of metal atoms is rare. Herein, the engineering of the coordination environment of Mn atoms in manganese dioxides (MnO2 ) by using a triethanolamine (TEA) complex‐induced method is reported. The detailed experimental characterizations and density functional theory calculations show that the optimized Mn coordination environment with oxygen deficiency and more corner‐shared Mn–Mn shells results in apparent electron dislocation and forms an effective built‐in electrical field. As a result, the obtained MnO2 ‐TEA sample exhibits a high conductivity and an excellent ion diffusion capacity, with a remarkable specific capacitance of 417.5 F g −1 at 1 A g −1 . At the power density of 450.0 W kg −1, the fabricated asymmetric supercapacitor delivers the maximal energy density (57.4 Wh kg −1 ). This work not only provides an effective strategy of adjusting the coordination environment of metal atoms in metal oxides, but also presents a deeper understanding of the electronic structure dependent electrochemical performance of electrode materials. Abstract : A simple triethanolamine complex method can significantly enhance the capacitive performance of MnO2 by adjusting the coordination environment of the Mn atoms, in which oxygen deficiency and more corner‐shared Mn–Mn shells (Mn–Mn2) are introduced to delocalize electrons and form a built‐in electrical field in MnO2, realizing a high conductivity and an excellent ion diffusion capacity.